2015
DOI: 10.3906/elk-1404-287
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy integration in smart grids-multicriteria assessment using the fuzzy analytical hierarchy process

Abstract: Abstract:Unlike the traditional way of efficiency assessment of renewable energy sources integration, the smart grid concept is introducing new goals and objectives regarding increased use of renewable electricity sources, grid security, energy conservation, energy efficiency, and deregulated energy market. Possible benefits brought by renewable sources integration are evaluated by the degree of the approach to the ideal smart grid. In this paper, fuzzy analytical hierarchy process methodology for the integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…The impact of intermittency on penetration level has not been examined. Multi-criteria assessment of RES has been carried out by Janjic et al [33] and Tanwar and Khatod [34] using analytical hierarchy process. An integrated decision making planning approach has been proposed by Kazmi et al [35] which embeds MCDM with unanimous decision making for sizing and siting of PV and D-STATCOM.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of intermittency on penetration level has not been examined. Multi-criteria assessment of RES has been carried out by Janjic et al [33] and Tanwar and Khatod [34] using analytical hierarchy process. An integrated decision making planning approach has been proposed by Kazmi et al [35] which embeds MCDM with unanimous decision making for sizing and siting of PV and D-STATCOM.…”
Section: Literature Surveymentioning
confidence: 99%
“…Multi‐criteria assessment of RES has been carried out by Janjic et al. [33] and Tanwar and Khatod [34] using analytical hierarchy process. An integrated decision making planning approach has been proposed by Kazmi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Janjic et al [223] use a methodology based on fuzzy logic, and the authors take into account qualitative and quantitative criteria, as well as varied performance indicators in the SG.…”
Section: Multiple Criteria Decision Makingmentioning
confidence: 99%
“…The parity check matrix used in this study is shown in Eq. (10). The received code word (C) of 7 bits (information bits (K) + parity bits (H)) is multiplied by the transpose of the parity check matrix H, as shown in Eq.…”
Section: Hamming Decodermentioning
confidence: 99%
“…The basic components and technologies of a smart grid can be listed as smart production, smart stations, smart deployment, smart meters, integrated communication, and advanced control methods [1][2][3][4][5]. With these components and technologies, a smart grid provides many benefits, such as demand management, greater integration of renewable resources, efficient usage of renewable resources (on both the production and consumption sides), energy-saving and price advantages, and system balance [1,[6][7][8][9]10,11] All these benefits can be achieved with a reliable communication infrastructure. Therefore, error detection and correction become critical issues for a wireless sensor network (WSN)-based smart grid communication network.…”
Section: Introductionmentioning
confidence: 99%